The Warner brothers - Yogerst, Chris, 1983- (The University Press of Kentucky, 2023)
"One of the oldest and most recognizable studios in Hollywood, Warner Bros. is considered a juggernaut of the entertainment industry. Since its formation in the early twentieth century, the studio has been a constant presence in cinema history, responsible for the creation of acclaimed films, blockbuster brands, and iconic superstars. These days, the studio is best known as a media conglomerate with a broad range of intellectual property, spanning movies, TV shows, and streaming content. Despite popular interest in the origins of this empire, the core of the Warner Bros. saga cannot be found in its commercial successes. It is the story of four brothers--Harry, Albert, Sam, and Jack--whose vision for Hollywood helped shape the world of entertainment as we know it"-- Provided by publisher.
Keywords: Warner, Harry Morris, -- 1881-1958.; Warner, Jack L., -- 1892-1978.; Warner, Sam, -- 1887-1927.; Warner, Albert, -- 1883-1967.; Warner Bros. Pictures (1923-1967); Motion picture industry -- United States -- History.; Executives -- United States -- Biography.; Motion picture producers and directors -- United States -- Biography.; Motion picture studios -- California -- Los Angeles -- History.; Cinéma -- Industrie -- États-Unis -- Histoire.; Producteurs et réalisateurs de cinéma -- États-Unis -- Biographies.; Studios de cinéma -- Californie -- Los Angeles -- Histoire.; Film & Video.; PERFORMING ARTS.; Direction & Production.; History & Criticism.; BIOGRAPHY & AUTOBIOGRAPHY.; Executives; Motion picture industry; Motion picture producers and directors; Motion picture studios; California -- Los Angeles; United States; Electronic books.; Biographies; History; Biographies.